2011
DOI: 10.1016/j.tube.2011.10.021
|View full text |Cite
|
Sign up to set email alerts
|

OsmC proteins of Mycobacterium tuberculosis and Mycobacterium smegmatis protect against organic hydroperoxide stress

Abstract: Summary Bacterial antioxidants play a critical role in the detoxification of endogenously and host derived oxidative radicals during host-pathogen interactions. Recently, the osmotically induced bacterial protein C (OsmC) is included in the antioxidant category of enzymes as it shows structural and functional relationships with organic hydroperoxide reductase (Ohr) enzyme. A copy of the gene encoding OsmC is conserved across mycobacterial species, including Mycobacterium tuberculosis (Rv2923c) and M. smegmatis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 55 publications
(76 reference statements)
4
22
1
Order By: Relevance
“…The reduction of organic hydroperoxides t-BHP and CHP by rMG_427 is consistent with the known activities of Ohr/ OsmC proteins, which preferentially detoxify OHPs. In addition, the observation that MG_427 was able to reduce H 2 O 2 is consistent with the reported property of OsmC from several bacteria (25,35,36).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The reduction of organic hydroperoxides t-BHP and CHP by rMG_427 is consistent with the known activities of Ohr/ OsmC proteins, which preferentially detoxify OHPs. In addition, the observation that MG_427 was able to reduce H 2 O 2 is consistent with the reported property of OsmC from several bacteria (25,35,36).…”
Section: Resultssupporting
confidence: 89%
“…We showed that purified rMG_427 protein responded to DTT and oxidant exposures and reduced OHPs and H 2 O 2 in a concentration-dependent manner. These results are consistent with the reported hydroperoxide peroxidase properties of OsmC proteins in E. coli (17,34), Thermus thermophilus (36), Thermococcus kodakarensis KOD1 (35), as well as M. tuberculosis and M. smegmatis (25). Further, we demonstrated that the ⌬MG_427 strain of M. genitalium exhibited hypersensitivity to t-BHP and increased sensitivity to H 2 O 2 and this sensitivity could be reversed in the mutant strain complemented with an intact MG_427 gene, similar to osmC mutants of E. coli (24) and M. smegmatis (25).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In case of atypical Mycobacterium species bacterial antioxidants are thought to modulate host derived oxidative killing mechanisms [19]. In Mycobacterium species new antioxidant mechanisms that protect the bacterium from the phagosomal respiratory burst is an established phenomenon [20,21]. Even recombinant BCG over-expressed with superoxide dismutase A confers less protection for development of tuberculosis [22].…”
Section: Tuberculosis and The Antioxidant Paradoxmentioning
confidence: 99%